КРЕАТИВНИЙ МАРКЕТИНГ ЯК ВАЖЛИВИЙ ІНСТРУМЕНТ ІННОВАЦІЙНОГО РОЗВИТКУ ЕКОНОМІКИ - Dembowska, Barbara; Kalinichenko, Olena; Poita, Iryna (Zhytomyr Ivan Franko State University, 2021)
The article identifies the most important areas of development of creative marketing, which are the result of creative "imagination" of the marketer. In essence, this is the freedom to make a marketing decision based on market conditions, experience, knowledge, consumer behavior in each market segment. Thus, a great responsibility in this case lies with the marketer, who must have a non-standard thinking, the talent to creatively perceive the situation in the market and use them, as well as be able to choose a non-traditional marketing option that would immediately attract consumers, make them stay longer near this product or its advertising. This is the main difference between creative and traditional marketing - the ability to attract the attention of the buyer, to surprise him. The marketer must have a lateral thinking, which is to shift from traditional thinking, breaking the standard approaches to any particular idea, finding an original way to express it, creating something radically new. The article proposes a synthetic technology of innovation, which includes all components of the socio-economic system: society, economy and society and creates a sequence. It is proved that the use of a creative marketing approach is reflected in the product and its characteristics: novelty of the product, non-standard product, purposefulness in use, development. The article reveals the essence, advantages and disadvantages of implementing creative marketing strategies, including anticipation strategy and reactive strategy. Introduction and use of a creative approach to marketing activities of the enterprise is a key element of modern entrepreneurship, which plays a key role in achieving goals. The right combination of creative approach and pragmatic view is the key to the effective functioning of the enterprise in modern market conditions.